Oral cefuroxime axetil compared with oral ampicillin in treating acute uncomplicated gonorrhoea. - Wanas, T M (1986)
The efficacy and tolerance of single oral doses of cefuroxime axetil (1.5 g) were compared with oral ampicillin (3 g) for treating acute gonococcal urethritis in 110 men and 30 women. Each dose was given with 1 g probenecid. Of the 62 assessable patients who received ampicillin, two failed to respond to treatment. Of 67 assessable patients who received cefuroxime axetil, one failed to respond. Pencillinase producing strains of Neisseria gonorrhoeae were isolated from five patients; one received ampicillin and failed to respond, whereas the other four received cefuroxime axetil and three were cured. A single oral dose of 1.5 g cefuroxime axetil with 1 g probenecid seemed to be an effective treatment for acute gonococcal urethritis, especially for penicillin resistant strains.